Transformasi Otoritas Keagamaan di Era Dakwah Viral: Kajian Mediatization of Religion dengan Perspektif Etik Mahabbah Rabi‘ah al-‘Adawiyah - Muhammad Arifin (Ushuluna: Jurnal Ilmu Ushuluddin, 2025)
This study examines the transformation of religious authority in the era of viral digital da’wah through the perspective the Mediatization of Religion and analyzes the relevance of Rābi‘ah al-‘Adawiyah's concept of mahabbah as an ethical framework for da'wah amid the dominance of social media. This research employs a qualitative library research approach, using primary sources on the Mediatization of Religion and the thought of Rābi‘ah al-‘Adawiyah, while secondary sources consist of empirical studies on da'wah practices across social media platforms. The findings reveal that the process of mediatization has transformed the legitimacy of religious authority from one primarily grounded in scholarly competence to one increasingly shaped by media logic, including algorithms, popularity, and digital performativity. In this context, Rābi‘ah al-‘Adawiyah's concept of mahabbah offers an ethical perspective that emphasizes da'wah should be grounded in sincerity and pure love for God rather than the pursuit of popularity. The integration of these two perspectives provides an ethical framework for da'wah that strengthens the integrity of religious authority in the dynamic landscape of digital media.